4th Agriculture and Rural Development Day, 18 June 2012 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
On June 18 2012, in connection to the Rio+20 United Nations Conference on Sustainable Development, CGIAR Climate Change, Agriculture and Food Security (CCAFS) and partners hosted the 4th Agriculture and Rural Development Day at the SulAmerica Convention Center in central Rio. The purpose of ARDD was to ensure that the vision for a sustainable green economy from Rio+20 included clear steps for building a sustainable food system. The event featured keynote speeches, high-level panels, parallel learning events and an exhibition.